Effects of aqueous and ethanolic extracts of Lepidium meyenii Walp (red and black maca) on Caenorhabditis elegans - Paternina-Ricardo, Saray; Salgado, Barbara Arroyo; Espiñeira, Maria Cecilia García (Acta Scientiarum. Biological Sciences, 2022)
Lepidium meyenii (maca) is a Peruvian nutraceutical plant, whose hypocotyl has a variety of colors ranging from black to white. The black and red varieties of maca have been the most studied since their extracts are associated with effects such as increased sperm count, decreased glucose levels, reversal of prostatic hyperplasia, among others. However, the properties related to reduction of oxidative stress, metabolic diseases and anti-aging have not yet been confirmed. The aim was to evaluate the effects of aqueous and ethanolic extracts, obtained from spray-dried hydroalcoholic extract of hypocotyl of black and red maca (Lepidium meyenii), on mortality, growth, reproduction, lipid accumulation and the expression levels of genes related to oxidative stress and heat shock, in the in-vivo model, Caenorhabditis elegans (C. elegans), using different concentrations. The results showed that maca extracts were not toxic to the model at concentrations below 100 mg L-1. However, higher concentrations caused high mortality, growth disturbances, oxidative stress and lipid accumulation. Black maca extracts increased the reproduction of C. elegans by increasing the number of offspring in C. elegans, both in aqueous and ethanolic extracts. On the other hand, ethanolic extracts produced an increase in the expression of genes related to oxidative stress, indicating a mild stressor behavior of the same. C. elegans represents an established model for evaluating the biological properties of nutraceutical plants of biological interest and can be used in the search for antioxidant activity of L. meyenii (hypocotyl), as well as it can be used in future studies to identify some metabolites involved in each biological property and to understand the biochemical and molecular mechanisms involved in these properties.